The Comparison of Visual Acuity After Congenital Cataract Surgery between Children ≤2 Years and >2-17 Years - Adam Surya Romadhon; Joni Susanto; Rozalina Loebis (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Introduction: Congenital cataract is turbidity occurs in eye lens that present at birth or immediately after. We aim to find out visual acuity after congenital surgery between children under 2 years old and 2-17 years old after following up 3, 6, 12 months.Methods: This was a cross-sectional study. Data were gathered from medical record of congenital cataract aged ≤2 years and >2-17 years including age of surgery, frequency of eyes, sex, laterality, and visual acuity of patients with best corrected visual acuity (BCVA). All data analyzed using Mann-Whitney test.Results: 41 children (67 affected eyes) in which 45 eyes that were operated at aged ≤2 years and 22 eyes were operated at aged >2-17 years. There was average difference of visual acuity between age group of ≤2 years and >2-17 years while following-up 3 months (1.60 ± 0.34 logMAR, 1.23 ± 0.67 logMAR, p = 0,003). Whereas in follow up 6 months (1.23 ± 0.47 logMAR, 1.15 ± 0.68 logMAR, p = 0,242) and 12 months (0.94 ± 0.47 logMAR, 0.96 ± 0.44 logMAR, p = 0,840), there were no difference significant average of visual acuity.Conclusion: Visual acuity after following-up 3 and 6 months in age group of >2-17 years were better than age group of ≤2 years, whereas after following-up 12 months in age group ≤2 years, it was obtained that visual acuity was better than age group of >2-17 years.